To Go or Not to Go: Does Linking Intelligence and Wisdom Provide a More Powerful Theoretical Lens for Understanding Learning in Adulthood? - Rosemary S. Caffarella (Adult Education Research Conference, 2007)
I first argue that being intelligent, no matter how defined, is not enough to address the complexity of problems and challenges we face in the 21st century. I then explore whether linking selected concepts of intelligence and wisdom might provide a more robust way for educators to view the power of thinking that adult learners possess.